2012
DOI: 10.1891/0886-6708.27.6.941
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Preschool Children’s Attitudes and Beliefs About Intimate Partner Violence

Abstract: Few studies have considered how intimate partner violence (IPV) impacts children's overarching attitudes and beliefs about the prevalence and acceptability of aggression. This pilot study included 92 preschool children exposed to IPV who reported on attitudes and beliefs about violence using a new, theoretically driven measure. Findings illustrate that preschoolers were able to respond reliably on this measure, and that most report at least one maladaptive attitude or belief about violence. Maternal posttrauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…For example, Fosco, DeBoard, and Grych (2007) reported that children who had witnessed violence between parents consider, according to their explanations, that the perpetrator has temporarily lost control, that the partner provoked the perpetrator in some way, that the victim refused to do something that the aggressor wanted, that alcohol had generated it, or even that there were particular characteristics-impossible to be managed-inside the aggressor, that had caused the violence episode. This could also be associated with findings that maintain that from earlier stages such as preschool, children who are exposed to violence between parents develop distorted views about acceptance of violence, and start to believe that it is a usual behavior, justifiable, and often the only way to solve problems (Howell, Miller, & Graham-Bermann, 2012;Jouriles et al, 2012;. Even though these studies are contextualized in families where children have witnessed violence among their parents, these data are consistent with the findings of the present research.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Fosco, DeBoard, and Grych (2007) reported that children who had witnessed violence between parents consider, according to their explanations, that the perpetrator has temporarily lost control, that the partner provoked the perpetrator in some way, that the victim refused to do something that the aggressor wanted, that alcohol had generated it, or even that there were particular characteristics-impossible to be managed-inside the aggressor, that had caused the violence episode. This could also be associated with findings that maintain that from earlier stages such as preschool, children who are exposed to violence between parents develop distorted views about acceptance of violence, and start to believe that it is a usual behavior, justifiable, and often the only way to solve problems (Howell, Miller, & Graham-Bermann, 2012;Jouriles et al, 2012;. Even though these studies are contextualized in families where children have witnessed violence among their parents, these data are consistent with the findings of the present research.…”
Section: Discussionsupporting
confidence: 90%
“…Such as, having an age-appropriate interview room, having the child’s preferred gender to talk with during the interview and ensuring that the person bringing the child to the interview is actually a good support (Allnock and Miller 2013 ). In Howell et al’s study ( 2012 ), children who felt comfortable showed more ability to engage and better comprehension of what was being asked of them. Similarly, Berson and Meisburger ( 1998 ) found that children needed to feel safe and protected in their immediate environment in order for them to disclose.…”
Section: Findings From the Literaturementioning
confidence: 97%
“…• the degree to which social behaviors are defined as appropriate under various circumstances • the level of shared agreement as to culturally justifiable behavioral expressions • patriarchal-matriarchal (and alternative) belief systems • the legitimization of different power dynamics • the cultural acceptability of violence Wherever human beings engage in IA, the interpretive component of the social exchanges must be considered to determine the degree to which the actions are considered legitimate and justifiable by those directly involved and any observers (including those who become aware of the events only after the fact). The learning aspect of the justification process commences early on in life, such that even pre-school children have developed clear ideas about the acceptability of aggression and violence under various circumstances (e.g., Howell et al 2012, Swit et al 2016.…”
Section: Level Iii: Cultural Justification Frameworkmentioning
confidence: 99%